How to Differentiate Recurrent Deep Vein Thrombosis from Postthrombotic Syndrome - Gautam, Gargi; Sebastian, Tim; Klok, Frederikus A. (Hämostaseologie, 2020)
Venous thromboembolism (VTE) is associated with significant morbidity and mortality. Accuracy of diagnosis is thus of vital importance. Failure to diagnose VTE increases the risk of progression and complications. Conversely, anticoagulation as a result of an incorrect diagnosis exposes patients to the associated hazards of bleeding. The diagnostic management of recurrent deep vein thrombosis (DVT) and postthrombotic syndrome (PTS) is especially challenging due to the lack of well-established diagnostic standards. Particularly, the differentiation between the two is notoriously difficult as symptoms, clinical signs, and diagnostic test findings largely overlap. This review highlights the current diagnostic and management strategies for recurrent DVT and PTS with a focus on clinical findings and imaging modalities. We also discuss current open questions for clinicians in the field, anticipating future directions and predictions for the year 2050.
Keywords: venous thromboembolism; deep vein thrombosis; recurrent VTE; postthrombotic syndrome